Biofilm formation and genetic characterization of New Zealand Cronobacter isolates. Issue 2 (28th December 2017) - Gupta, Tanushree B.; Mowat, Eilidh; Brightwell, Gale; Flint, Steve H.
Abstract: The study aimed to determine genetic diversity of a collection of New Zealand Cronobacter isolates collected from different sources and their ability to form a biofilm on different materials under different conditions. Isolates were screened for the presence of biofilm associated genes. Furthermore, suppression subtractive hybridization (SSH) was used to identify unique genes, present in a C. sakazakii strain (isolate ES191) which forms a stronger biofilm than the reference strain C. sakazakii BAA894. Results indicated that New Zealand Cronobacter spp. strains were genetically diverse. Biofilm formation was both temperature and nutrient dependent and varied widely within and between clinical, dairy, and environmental isolates. Moreover, C. akazakii adhered more to polyvinyl chloride followed by silicone, polyurethane and stainless steel and all the isolates harbored biofilm related genes. Of the 72 PCR products sequenced from the SSH library, 16 unique gene sequences were identified, of which nine were expressed only in ES191 and were found to be involved in hypothetical protein, energy production, and virulence. This study suggests the choice of enteral neonatal feeding tube material could dramatically influence the attachment, growth, and biofilm formation of C. sakazakii . Practical applications: The present study showed variable ability of Cronobacter species to form biofilms in different matrices tested. It was observed that environmental strains have a greater ability to persist and one of these formed stronger and complexed biofilm, which may increase the food safety risk. This calls for undertaking appropriate clean in place treatment regimes well efficient to remove strong and complex biofilms. Research findings of this study showed that both PVC and silicone based tubing represent higher risk materials for the colonization of C. sakazakii and subsequent development of biofilms. Therefore, it is imperative to carefully select a tubing material which is less likely to support the attachment and development of biofilms. However, the most practical means of reducing the risk of C. sakazakii infection is by using sterile ready‐to‐use formula and maintaining a clean environment when reconstituting the formula milk.